SENI DAN ESTETIKA (KEINDAHAN) DALAM PERSPEKTIF MUHAMMAD IQBAL - Rahmat, Rahmat; Soleh, Achmad Khudori (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2025)
Art and aesthetics involve the analysis of values, tastes, attitudes, and standards that shape an individual's experience and judgment of human-made creations or the beauty found in nature. The purpose of this article is to present an understanding of art and aesthetics based on the thoughts of Muhammad Iqbal. This study employs a qualitative library research approach by reviewing relevant literature. Additionally, a historical approach is used to examine the concept of art and aesthetics from Muhammad Iqbal’s perspective. The data are obtained from previous scholarly works, including journal articles and books related to the subject matter, followed by an analysis of Muhammad Iqbal's historical background and his concept of art and aesthetics to draw conclusions.  The findings of this study reveal that: (1) According to Muhammad Iqbal, the core and foundation of human life organization is the ego, which encompasses the entirety of thought and awareness about life, while art and beauty are integral parts of human existence. Iqbal’s thoughts on aesthetics (beauty) and the philosophy of *khudi* originate from Islamic teachings as well as Western philosophical influences. (2) Iqbal has a unique perspective on art and beauty, emphasizing vitality and functionality, making them dynamic and full of the spirit of struggle. (3) In his view, something can be considered aesthetic if it meets at least two essential elements: first, expression, which refers to the originality of the artwork itself; and second, purpose, where one of the objectives of art is to contribute to the development and cultivation of society.